An Urgent Human Health Dilemma Facing Refugees and their Host Caregivers? - Michael, Silbermann; Lea, Baider; Daniela, Respini; Paolo, Tralongo; Michel, Daher; Rana, Obeidat; Nahla, Gafer; Samaher, Abdul Razzaq Fadhil; Maryam, Rassouli; Simone, Cheli DPSy; Alexander, Eniu (Journal of Human Health Research, 2018)
The continuous waves of refugees from Africa and the Middle East to Europe present major inter¬cultural challenges to European health professionals and to society at large. A recent workshop in Sicily brought together local physicians, nurses, psychologists and managers of governmental agencies, along with representatives from Lebanon, Israel, Iraq, Iran, Sudan, Tunisia, Jordan and the European Society of Medical Oncology (ESMO) to develop training programs aimed at formulating dialogue between regional professionals and refugees. A major barrier refugees face is a lack of verbal and cultural communication, which hinders their smooth absorption into the new society. Cultural mediators who speak Arabic and Italian and understand the refugees' faith, tradition and beliefs are vital to successfully build bridges of trust between caregivers and refugees. Most asylum seekers experience anxiety, fear, and depression upon arrival in Europe. To achieve trust, all workshop participants agreed to develop a palliative care model that would best suit the unique circumstances now facing some Mediterranean countries and assist in overcoming the suffering of refugees during their initial stay in Europe. Such a model would include bio-psychosocial elements, essential for a culturally sensitive approach and based on core ethical principles.
Keywords: Palliative care; Refugees; Middle East; North Africa; Europe